Differential stabilization by netropsin of inducible B-like conformations in deoxyribo-, ribo- and 2'-deoxy-2'-fluororibo-adenosine containing duplexes of (dA)n . (dT)n and (dA)n . (dU)na. - Zimmer, C (1982)
Six polynucleotide duplexes containing polydeoxyadenylic acid, polyadenylic acid or poly-2'-deoxy-2'-fluoro-adenylic acid in one strand, and polydeoxyuridylic acid or polydeoxythymidylic acid in the other strand have been studied by circular dichroism, ionic strength dependence of melting temperatures and binding of the DNA specific antibiotic netropsin. Circular dichroism spectra of (dA)n . (dT)n and (dA)n . (dU)n indicated the presence of the B-form of DNA, while those of (dAfl)n . (dT)n and (rA)n . (dT)n (and the corresponding (dU)n hybrids) indicated the presence of the A-form. (dAfl)n . (dT)n and (dAfl)n . (dU)n bound netropsin only slightly less than the (dA)n containing duplexes, while replacement by (rA)n decreased netropsin binding to a large degree. Since netropsin requires B-DNA for binding, it is concluded that the A to B transition is facilitated in the case of fluorine substitution in the sugar moiety, while the 2'-OH group greatly limits this conformational change.